School Students’ Perceptions on School Management and Pedagogical Approaches - Acharya, Bisna (International Journal of Atharva, 2024)
This study investigates students' perspectives on teaching-learning pedagogy and school management techniques. The information was collected from 240 students attending schools in urban, suburban, and rural areas, across different grade levels. To get this data, a variety of research techniques were combined. Through surveys, interviews, and focus groups, the study looked at students' attitudes, beliefs, and experiences in the classroom. The results provide a comprehensive understanding of students' viewpoints on a range of school administration topics, such as classroom dynamics, teacher-student interactions, administrative policies, and the use of technology in the classroom. Ann extensive analysis was conducted to obtain a comprehensive understanding of students' inclinations, difficulties, and recommendations concerning instructional strategies, evaluation procedures, and the school's general ethos. The study underlines the value of taking into account students' opinions when making decisions about education and stresses the necessity of creating a welcoming and stimulating learning environment that can accommodate a wide range of learner needs. The implications for educators, policymakers, and school administrators are examined in this paper. It makes recommendations for improving teaching-learning pedagogies and school management techniques to support student engagement, academic achievement, and general well-being.